Algoritmos de busca de caminho em Tile Games - (:unkn) unknown (Universidade Federal do Pampa, 2013)
One of the most desired features in a game is a representation of reality. It is not enough to just move the player, it is necessary that the other characters act according to what is expected of them if the game environment was the real world. For this, various algorithms are used to help the "perception" of the environment, drive and achievement of goals by the NPCs (Non Player Characters). It is noteworthy that this "expectation" is independent of the platform on which the game is installed, i.e., it is expected that a character from a browser game is as smart as one who belongs to a particular platform exclusive for games and with hardware suitable for this activity. The objective of this work is to apply pathfinding algorithms in games that use platforms with limited resources, such as tablets and phones, and thus obtain an analysis of which are most suitable, either in terms of time, memory, or optimality. The prototypes developed to test these algorithms will be built from the Tile method.. This method aims to reduce the amount of memory used by the game, by splitting large images into several smaller parts, which are replicated as needed to reproduce the original image.
Keywords: Computer science; Artificial intelligence; Algorithms; Games; Tile Games; Ciência da computação; Inteligência artificial; Algoritmos; Jogos; Tile Games; CNPQ::CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO